2019
DOI: 10.1073/pnas.1904493116
|View full text |Cite
|
Sign up to set email alerts
|

Protective role for the N-terminal domain of α-dystroglycan in Influenza A virus proliferation

Abstract: α-Dystroglycan (α-DG) is a highly glycosylated basement membrane receptor that is cleaved by the proprotein convertase furin, which releases its N-terminal domain (α-DGN). Before cleavage, α-DGN interacts with the glycosyltransferase LARGE1 and initiates functional O-glycosylation of the mucin-like domain of α-DG. Notably, α-DGN has been detected in a wide variety of human bodily fluids, but the physiological significance of secreted α-DGN remains unknown. Here, we show that mice lacking α-DGN exhibit signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Furin protease belongs to the family of calcium (Ca 2+ )-dependent proprotein/prohormone convertases (PCs) that are ubiquitously expressed in humans, and its levels are significantly elevated in lung cystic fibrosis. 15 Furin protease also cycles among the trans-Golgi network (TGN), the cell membrane (viral attachment), and endosomes (viral translocation in the endosomes). Furin recognizes the R-X-K/R-R motif and cleaves the peptide in the presence of Ca 2+ 16 , 17 and is also known for cleaving different viral (influenza and HIV) envelope glycoproteins, thereby enhancing fusion of the virus with the host cell membrane.…”
mentioning
confidence: 99%
“…Furin protease belongs to the family of calcium (Ca 2+ )-dependent proprotein/prohormone convertases (PCs) that are ubiquitously expressed in humans, and its levels are significantly elevated in lung cystic fibrosis. 15 Furin protease also cycles among the trans-Golgi network (TGN), the cell membrane (viral attachment), and endosomes (viral translocation in the endosomes). Furin recognizes the R-X-K/R-R motif and cleaves the peptide in the presence of Ca 2+ 16 , 17 and is also known for cleaving different viral (influenza and HIV) envelope glycoproteins, thereby enhancing fusion of the virus with the host cell membrane.…”
mentioning
confidence: 99%
“…Strikingly, compared with RaTG13, we found an additional PRRA sequence at the F1 site of SARS-CoV-2 forming a strong and reliable FCS (Furin score 0.62). Although the source of insertion was unknown, the PRRA sequence was common to avian influenza virus [29]. We deduced that it might have been inherited from HKU1 and OC43, which had effective FCS at the F1 site (Furin score 0.878 and 0.744) and the respective amino acid sequence of SSRRKRR and TKRRSRR, with high similarity of NSPRRAR in SARS-CoV-2.…”
Section: Evolutionary Divergence In Sars-cov-2 Is Strongly Correlatedmentioning
confidence: 98%
“…Among ZJ01 unique mutations, 10 (NO. [22][23][24][25][26][27][28][29][30][31] were located on the S protein, including 3 samesense mutation, 2 deletion mutation and 5 missense mutation, which led to amino acid changes of Ser596, Gln613, Glu702, Ala771, Ala1015, Pro1053 and Thr1066. Further similarity analysis indicated that the main difference among various coronaviruses located in the Receptor Binding Domain (RBD) region of S1.…”
Section: Sars-cov-2mentioning
confidence: 99%
“…Strikingly, we found an additional PRRA sequence in the F1 site of SARS-CoV-2 when compared with RaTG13, forming a strong and reliable FCS (Furin score 0.62). Though the source of insertion was unknown, the PRRA sequence was common in Avian Influenza virus 29 . We deduced that its source might inherit from is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint HKU1 and OC43, which had effective FCS in F1 site (Furin score 0.878 and 0.744) and respective amino acid of SSRRKRR and TKRRSRR, with high similarity of NSPRRAR in SARS-CoV-2.…”
Section: Evolutionary Divergence In Sars-cov-2 Strongly Correlated Wimentioning
confidence: 99%